Literary communication in Song Dynasty - Wang, Zhaopeng, 1959-; Zhu, Wei (College teacher); Li, Minjie; Wang, Zhaopeng, 1959- (London : Routledge, Taylor & Francis Group, 2024)
Based on first-hand historical materials, this book explores the various aspects of literary communication during the Song Dynasty in China. The book investigates the single-channel dissemination of poetry and ci works, the dissemination of literary collections, the dissemination through wall inscriptions, the oral dissemination of Song ci, the remuneration and commercialization of literature in the Song Dynasty, the paths to fame for Song writers, the non-literary factors in the dissemination of literature and the dissemination of literary works through paintings and songs. The author provides insights into the six major questions in the study of literary communication: Who disseminates, where, how, what, to whom and the effects of dissemination. The author also seeks to provide detailed answers to the following questions. What was the role of female singers in both domestic and official entertainment? What were the costs and prices of the books? Who paid the authors? What methods did writers use to gain fame and social recognition? This work will be essential reading for scholars and students of Chinese studies, communication studies and media and cultural studies.
Introduction: Issues in Literary Communication Studies 1. The Spread of Single Pieces of Poems in Song Dynasty 2. The Spread of Poetry Anthologies in Song Dynasty 3. The Spread of Wall-inscribed Poems in Song Dynasty 4. The Spread of Poems by Singing and DancingGirls in Song Dynasty 5. The Remuneration for Writers in Song Dynasty 6. Dissemination Effects of Obtaining Recognition from Prominent Figures 7. Non-literary Factorsfor the Communication Effect of Literature 8. The Communication of Poetry through Paintings and Songs
Keywords: Chinese literature -- Song dynasty, 960-1279 -- History and criticism; LITERARY CRITICISM / Asian / Chinese; LITERARY CRITICISM / Poetry